VD_FINDINFO HC / 2015 / 144 vom 22. Januar 2015 - VD Tribunal cantonal (2015)
OBLIGATION D'ENTRETIEN, PROTECTION DE L'UNION CONJUGALE, CONJOINT, DROIT DE GARDE, PROTECTION DE L'ENFANT, AUDITION DE L'ENFANT, COMPÉTENCE RATIONE MATERIAE | 176 al. 1 ch. 1 CC, 176 al. 3 CC, 275 al. 1 CC, 315a CC, 296 al. 3 CPC (CH), 298 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 316 al. 3 CPC (CH)